NEREA AMORÓS ELORDUY - Architecture as a Way of Seeing and Learning. The built environment as an added educator in East African refugee camps - Sumpsi Sánchez, Miguel (ZARCH, 2024)
NEREA AMORÓS ELORDUYArchitecture as a Way of Seeing and Learning. The built environment as an added educator in East African refugee campsUCL Press, London, 2021. 200 pp. Tapa blanda, 45,00 £PDF disponible online: Architecture as a Way of Seeing and Learning: The built environment as an added educator in East African refugee camps - UCL DiscoveryIdioma: inglésISBN (Pbk.): 978-1-80008-012-6ISBN (PDF): 978-1-80008-011-9